Buddhism in Vietnam - Minh Chi.; Hà Văn Tấn.; Nguyễn Tài Thư. (Hà Nội : Thế giới, 1999)
Introduction and dissemination; A period of prosperity for buddhism; Confucian predominance; Division of the country under the feudal system; A period of decline for the monarchical state.
Keywords: Religion; Buddhism; Buddhism -- Vietnam